2011
DOI: 10.1103/physrevlett.106.125504
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Nanoscale Mechanical Heterogeneity in a Metallic Glass by Dynamic Force Microscopy

Abstract: We report nano-scale mechanical heterogeneity of a metallic glass characterized by dynamic force microscopy. Apparent energy dissipation with the variation of ~12%, originating from non-uniform distribution of local viscoelasticity, was characterized.The correlation length of heterogeneous viscoelasticity was measured to be ~2.5±0.3 nm, which is well consistent with the dimension of shear transformation zones for plastic flow. This study provides the first experimental observation on the nano-scale mechanical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
206
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 372 publications
(232 citation statements)
references
References 34 publications
(73 reference statements)
17
206
1
2
Order By: Relevance
“…S3 (a 3D view from outside the MD box is in Fig. S4), in terms of property (soft spots) and corresponding structure (GUMs), may also help explain the origin of the heterogeneity in local elastic modulus and local viscoelasticity recently mapped out in experiments (26)(27)(28).…”
Section: Significancementioning
confidence: 93%
“…S3 (a 3D view from outside the MD box is in Fig. S4), in terms of property (soft spots) and corresponding structure (GUMs), may also help explain the origin of the heterogeneity in local elastic modulus and local viscoelasticity recently mapped out in experiments (26)(27)(28).…”
Section: Significancementioning
confidence: 93%
“…Whereas those studies have offered insight into the details of the atom rearrangement under an imposed shear stress for specific interatomic potentials, the system sizes are small and the strain rates are exceedingly high so that the direct application of the findings to actual experimental conditions is somewhat unclear. Moreover, recent experimental studies have revealed the presence of nanoscale spatial heterogeneities in amorphous alloys that have not been considered in the simulations, but may affect deformation (21)(22)(23)(24)(25)(26).…”
mentioning
confidence: 99%
“…83 With the single cycle method however, and by monitoring the wave prole of the cantilever at a nite number of locations on its longitudinal axis, transient phenomena can be probed, in principle, with sub-microsecond resolution. A discussion about the high temporal resolution of the method is given in terms of its potential to be employed experimentally to probe fast processes from those involved in phase transformation 84 and other irreversible interactions 23 to complex and fast biological phenomena. 9,81,85,86 In the conclusions, the experimental challenges involving implementation are put into context and related to current developments in advanced dAFM methods.…”
mentioning
confidence: 99%